A Supplement to Nehamas’s Reading of Nietzsche: The Evolution of Nietzsche’s Views on Self-Fashioning - Čukljević, Filip (Revista de Filosofía, 2025)
The aim of this paper is to supplement Alexander Nehamas’s aestheticist interpretation of Friedrich Nietzsche’s views on self-fashioning by exploring the evolution of these views from Nietzsche’s early thoughts about the significance of art to life, and by exploring some continuities and differences between this early Nietzsche’s thoughts and Nehamas’s understanding of mature Nietzsche. First, I will argue that the idea of self-fashioning consists of active and passive aspects united in a particular way. Nietzsche entertained both of these aspects in his earlier writings but did not arrive at their synthesis yet. Then I will investigate the unconscious dimension of self-fashioning, as suggested by Nehamas’s Nietzsche, and its relation to the unconscious dimension of Dionysian artistic power, introduced by early Nietzsche. Afterwards, we will see how this project of self-fashioning could be justified within Nietzschean perspective. Finally, it will be shown to what extent such project is “classical”.